The use of a weighted affective lexicon in a tutoring system to improve student motivation to learn. Issue 5 (29th October 2019) - Jiménez, Samantha; Juárez‐Ramírez, Reyes; Castillo, Víctor H.; Ramírez‐Noriega, Alan; Quezada, Ángeles
Abstract: In recent years, several educational systems have integrated text‐based affective feedback. However, analyses of the educational lexicon from the affectivity perspective are scarce. The provision of affective support by these systems is significant because it improves student motivation to learn. This study analyzes the use of a weighted affective lexicon in tutoring systems to improve student motivation. First, based on the suggestions of 166 undergraduate students, this study constructed and evaluated an educational lexicon in Spanish. Additionally, after considering the assessment of another group of 185 undergraduate students, this study provides an interpretation of words/phrases on a valence and arousal scale. The authors carried out a comprehensive analysis to categorize the words/phrases. Furthermore, this study integrates an affective lexicon in a tutoring system. Finally, this paper presents a review of the impacts of this system on the motivation of its potential users. The authors believe that the results of the present study will support the development of a highly adopted Intelligent Tutoring Systems (ITSs), which will benefit prospective users.